(untitled) - Martin, James (Upper Saddle River, N.J., 1996)
The second of three titles in James Martin's new computing Bible on enterprise computing. The last book showed how to bring database information to the desktop PC. This title takes up the software applications required to make networking happen: TCP/IP, etc. Perfect for those who need to understand the basics including network managers, MIS people, and software developers.
Keywords: Mạng cục bộ (Mạng máy tính),Local area networks (Computer networks